KEPELBAGAIAN PENGURUSAN SEKOLAH AGAMA RAKYAT DI MALAYSIA (Diversity of Community Religious School Management in Malaysia) - Siren, Nor Raudah Hj; Abdul Ghani Azmi, Ilhaamie; Abdul Jalil, Siti Jamiah Binti; Ab Majid, Azrin (Journal of Al-Tamaddun, 2018)
Community Religious School or well known as SAR is one of the Islamic education institutions that functions in developing human capital in Malaysia. The rapid growth of SAR in each state in Malaysia indicates that this institution has obtained good acceptance from the public and it is actually a necessity for Islamic education in this country. However, there is diversification of SAR management in each state that results in imbalance of the growth of SAR in this country. There have been advancing and declining of SARs in Malaysia. Thus, this research will review the background of SAR, its place in Malaysian law and how SAR is managed in each state. The methodology that is used in collecting the data is through documentation and interview with the concerned organizations at federal and state level that are involved with SAR management and interview the manager or leader (mudir) of SAR. Research has found that SAR is an institution that is based on religious syllabus that is fully managed by the Council of School Affairs and it is private. The structure of SAR management is different according to each state, either it is handled by State Department of Islamic Affairs, State Islamic Religious Council, NGOs and Islamic Foundation.